15 years of research on systemic risk across the globe: The evolution of the field and its drivers - Mikhail Stolbov; Maria Shchepeleva (Research in Globalization, 2024)
This study examines the evolution of research on systemic risk during the 2007–2021 period, encompassing the Global Financial Crisis, European financial crisis, the outbreak of the COVID-19 and a number of other notable episodes undermining global financial stability. Our research goal is two-fold. First, based on Scopus-indexed publications, we identify the most impactful countries, institutions and scholars in the field, revealing a gradual but notable decline in the annual shares of publications on systemic risk associated with major advanced economies. This is offset by the increasing role of emerging markets, primarily, China, which makes this research field more competitive. Second, we are also concerned with the drivers of research on systemic risk in a vast sample of countries during the observation period. By applying a combination of variable selection techniques to 33 indicators that can potentially incentivize research on systemic risk, we find that low bank profitability as well as the general productivity of economic research are the most robust factors stimulating such publications. A higher country’s score on the global innovation index also spurs the research in this field. Conversely, countries with a higher power distance index, i.e favoring hierarchy and low risk-taking, tend to produce less research on systemic risk.